Analysis of self-management ability, level of hope, and influencing factors in patients with prophylactic enterostomy for rectal cancer - Wang Xihua; Lin Guole; Cheng Yue; Li Min; Lu Qiaodan; Guo Shuli; Cheng Long; Sun Wei; Sheng Yu (结直肠肛门外科)
[Objectives] To investigate the self-management ability and level of hope in patients with prophylactic enterostomy for rectal cancer, and analyze the influencing factors. [Methods] A cross-sectional study was conducted using convenience sampling. A total of 126 patients who underwent prophylactic enterostomy after radical resection for rectal cancer at the Department of Basic Surgery, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences, from March to November 2022 were recruited. General information of the patients was collected, and a questionnaire and a scale were used to assess their self-management ability and level of hope, respectively. The influencing factors were analyzed. [Results] The patients’average score on the self-management ability questionnaire with mean (SD) of 102.1 (12.2), indicating a moderate level. Age, residence, postoperative time interval, length of hospital stay, and primary caregiver influenced the patients’scores (P < 0.05). Age, postoperative time interval, length of hospital stay, and primary caregiver were independent influencing factors of the scores (P < 0.05). The median score of the level of hope scale for the patients was 34 (34, 36), indicating a moderate level. Age, education level, postoperative time interval, and primary caregiver influenced the patients’scores (P < 0.05). The postoperative time interval was an independent influencing factor of the scores (P < 0.05). [Conclusion] The self-management ability and level of hope in patients with prophylactic enterostomy for rectal cancer were at a moderate level, both of which were influenced by the postoperative time interval. Age and primary caregiver were associated with the patients’self-management ability and level of hope.